2010
DOI: 10.1038/aps.2010.122
|View full text |Cite
|
Sign up to set email alerts
|

HPLC and LC-MS analysis of sinomenine and its application in pharmacokinetic studies in rats

Abstract: Aim: To improve and validate analytical methods based on HPLC and liquid chromatography coupled to electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) for the quantitative measurement of sinomenine in rat plasma and brain tissue. Methods: The separation of analytes and the internal standard (IS), chloramphenicol, was performed on an Agilent TC-C18 column (250×4.6 mm, 5 µm). Blood samples were measured with a Surveyor photodiode array (PDA) detector at a wavelength of 263 nm. The LCQ DECA XP Plus ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 13 publications
1
24
1
Order By: Relevance
“…It has been shown that intraperitoneally injected or orally administered sinomenine can reach the brain [39,40] suggesting that it can cross blood-brain barrier. In addition, intraperitoneally injected sinomenine confers protection in ischemic brain injury [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that intraperitoneally injected or orally administered sinomenine can reach the brain [39,40] suggesting that it can cross blood-brain barrier. In addition, intraperitoneally injected sinomenine confers protection in ischemic brain injury [41].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental studies using beagle dog models demonstrate that the absolute bioavailability of sinomenine is low, and the elimination of sinomenine tablet is fast . After the quantitative measurement of sinomenine, Long et al (2010) found that the numerical values are linear over the concentration range of 0.1-100 μg/mL for sinomenine in plasma and over the range of 0.01-5.00 μg/g for sinomenine in brain tissue. The extraction and recovery of sinomenine from plasma and brain tissue are 72.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Several liquid-liquid extractions or protein precipitation procedures [14][15][16][17][18][19][20][21][22] were exploited for plasma sample preparation. Acetonitrile, methanol and 7% perchloric acid were chosen and tested for protein precipitation because of high throughput characteristics and the suitable sensitivities obtained.…”
Section: Lc/ms/ms Optimization and Sample Preparationmentioning
confidence: 99%
“…Currently, the primary focus of quantification of sinomenine hydrochloride in biological samples is based on the high-performance liquid chromatography with ultraviolet detector (LC-UV) [14][15][16][17][18][19][20], which required either a complicated extraction or long analysis time (>10 min). Furthermore, the lower limits of quantitation (LLOQ) of these methods in a range of 6-320 ng/mL were not suitable for sinomenine pharmacokinetic study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation